Creatine supplementation enhances muscular performance during high-intensity resistance exercise. - Volek, J. S.; Kraemer, W. J.; Buch, J. A.; Incledon, T.; Clark, K. L.; Lynch, J. M. (Journal of the American Dietetic Association, 1997)
OBJECTIVE: This study was undertaken to investigate the influence of oral supplementation with creatine monohydrate on muscular performance during repeated sets of high-intensity resistance exercise. SUBJECTS/DESIGN: Fourteen active men were randomly assigned in a double-blind fashion to either a creatine group (n = 7) or a placebo group (n = 7). Both groups performed a bench press exercise protocol (5 sets to failure using each subject's predetermined 10-repetition maximum) and a jump squat exercise protocol (5 sets of 10 repetitions using 30% of each subject's 1-repetition maximum squat) on three different occasions (T1, T2, and T3) separated by 6 days. INTERVENTION: Before T1, both groups received no supplementation. From T1 to T2, both groups ingested placebo capsules. From T2 to T3, the creatine group ingested 25 g creatine monohydrate per day, and the placebo group ingested an equivalent amount of placebo. MAIN OUTCOME MEASURES: Total repetitions for each set of bench presses and peak power output for each set of jump squats were determined. Other measures included assessment of diet, body mass, skinfold thickness, and preexercise and 5-minute postexercise lactate concentrations. RESULTS: Lifting performance was not altered for either exercise protocol after ingestion of the placebos. Creatine supplementation resulted in a significant improvement in peak power output during all 5 sets of jump squats and a significant improvement in repetitions during all 5 sets of bench presses. After creatine supplementation, postexercise lactate concentrations were significantly higher after the bench press but not the jump squat. A significant increase in body mass of 1.4 kg (range = 0.0 to 2.7 kg) was observed after creatine ingestion. CONCLUSION: One week of creatine supplementation (25 g/day) enhances muscular performance during repeated sets of bench press and jump squat exercise.